APLIKASI AKAD MURABAHAH PADA PORUDUK KONSUMTIF - Sartono Sartono; Lilis D. Hadaliah (Prodi Hukum Ekonomi Syariah (Muamalah), 2018)
Sales-based Akad Murabahah is expected to be a system solution for the results thattend to be high risk. The profit-making in front is actually valid and true according to Sharia,because Murabahah is a sales-based contract which means something oriented real.Research aims: 1) analyzing the activities of financial services developed by BMT Al-AmanahCiawi Tasikmalaya 2) analyzing consumptive products that can be facilitated by BMT AlAmanah Ciawi Tasikmalaya, 3) analyzing application Akad Murabahah in BMT Al-AmanahCiawi Tasikmalaya This research uses qualitative descriptive methods with the type of fieldresearch with inductive logic, namely observation of depiction and systematic data parsing.To help with data collection using observation methods, interviews, and documentation.Data analysis tools are qualitative descriptive. The result can be concluded: 1) The financial services activities in BMT Al-Amanah Ciawi Tasikmalaya are: financial storage and financialservices financing. 2) Consumptive product financing using the product of Ba'i alMusawwamah which is an application of Akad Murabahah, there are some provisionsregarding the desired product or needed. 3). BMT Al-Amanah Ciawi Tasikmalayaimplements the concept of trading contract (Murabahah) into 2 financing products namelyMurabahah products which is a product of goods financing or productive products